ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES AFTER COVID-19 - Bobokulova , Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Currently, issues related to the successful diagnosis and treatment of acute purulent-destructive lung diseases after suffering SARS-CoV-2 remain relevant due to their unresolved, preservation of significant morbidity, the severity of the course, possible complications, and an impressive number of deaths. The article provides an overview of the literature data indicating the high relevance of this problem to the present time.